Pengaruh KB Suntik DMPA Terhadap Gangguan Siklus Menstruasi pada Akseptor KB - Lilis Candra Yanti; Annisa Lamaindi (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; the use of injectable contraceptives can effectively prevent pregnancy up to 99%-100%, one of the side effects is the onset of irregular menstruation. Objectives; determine the effect of DMPA injection contraception on menstrual cycle disorders in family planning acceptors. Method; analytic observational research with cross-sectional design, sampling using total sampling. Results; show that there is an effect of duration of use with menstrual cycle disorders DMPA family planning acceptors with p-value = 0.036. Conclusion; that there is an effect of duration of use with menstrual cycle disorders DMPA family planning acceptors. The longer the use of DMPA contraception, the menstrual cycle disorders will occur